Modulation of Biomass Accumulation and Yield Traits in Vigna sinensis L. Under Paclobutrazol and NPK Phonska Plus (15:15:15) Treatments - Marvin Julius Siagian; Yonny Koentjoro; Puji Lestari Tarigan (Universitas Labuhanbatu, 2025)
The productivity of long beans (Vigna sinensis L.) in Indonesia remains low due to an imbalance between vegetative and generative growth, with long bean production experiencing significant fluctuations between 2017 and 2022, dropping to 352,700 tons in 2019 and rising again to 360,674 tons in 2022. Research on the use of paclobutrazol and NPK fertilizer on long beans is generally conducted separately, so information regarding their interaction on fruit set and productivity remains limited. Therefore, this study aims to evaluate the interaction between paclobutrazol concentration and Phonska Plus NPK fertilizer dose on the growth and yield of long beans (Vigna sinensis L.), as well as to determine the most effective treatment combination for improving the plants' generative performance. The study employed a two-factor randomized block design (RBD) with four levels of paclobutrazol (0, 100, 150, 200 ppm) and four levels of Phonska Plus NPK fertilizer (250, 300, 350, 400 kg/ha), each replicated three times. Data were analyzed using analysis of variance (ANOVA) and followed by a BNJ test at the 5% level if significant effects were found. The results showed significant interactions for plant height at 14 and 56 days after sowing (DAS), pod number in the 2nd and 3rd weeks of harvest, pod weight per plot, and fruit set. The combination of 150 ppm paclobutrazol and 400 kg/ha NPK Phonska Plus yielded the highest fruit set at 86.92% and high pod weight. Physiologically, a moderate dose of paclobutrazol effectively suppressed vegetative growth in a controlled manner, allowing for more efficient distribution of photosynthates to the generative organs, while sufficient levels of N, P, and K enhanced photosynthetic activity and the pod-filling process. This study demonstrates the synergy between hormonal regulation and balanced fertilization in enhancing the generative performance of long beans, and provides recommendations for effective dose combinations to support more efficient and targeted productivity improvements